1999
DOI: 10.1002/(sici)1096-8644(1999)110:29+<73::aid-ajpa4>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting sex differences in enamel hypoplasia in human and non-human primates: Developmental, environmental, and cultural considerations

Abstract: The purpose of this review is to provide a synoptic, critical evaluation of the evidence of, and potential etiological factors contributing to, sex differences in the expression of enamel hypoplasia (EH). Specifically, this review considers theoretical expectations and empirical evidence bearing on two central issues. The first of these is the impact of a theorized inherent male vulnerability to physiological stress on sex differences in EH. The second issue is the potential contribution to sex differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 154 publications
(218 reference statements)
3
62
0
3
Order By: Relevance
“…LHPC are focal, plane-form defects (Guatelli-Steinberg and Lukacs, 1999;Hillson and Bond, 1997) that manifest as pits of varying sizes in the enamel with occasional dentine involvement. In contrast to linear enamel hypoplasia (LEH), LHPC are non-linear, form on the facial aspect of the deciduous canines almost exclusively, and typically show no statistically significant differences between males and females within populations (Guatelli-Steinberg and Lukacs, 1999). These characteristics suggest that the etiology of LHPC is distinct from that of LEH.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…LHPC are focal, plane-form defects (Guatelli-Steinberg and Lukacs, 1999;Hillson and Bond, 1997) that manifest as pits of varying sizes in the enamel with occasional dentine involvement. In contrast to linear enamel hypoplasia (LEH), LHPC are non-linear, form on the facial aspect of the deciduous canines almost exclusively, and typically show no statistically significant differences between males and females within populations (Guatelli-Steinberg and Lukacs, 1999). These characteristics suggest that the etiology of LHPC is distinct from that of LEH.…”
Section: Introductionmentioning
confidence: 75%
“…One form of enamel defect, in particular, is well-suited for reconstructing prehistoric health experience because of its ease of observation, early age of formation, and linkages to clinical contexts dealing with modern health disparities; these are called localized hypoplasia of the primary canines (LHPC). LHPC are focal, plane-form defects (Guatelli-Steinberg and Lukacs, 1999;Hillson and Bond, 1997) that manifest as pits of varying sizes in the enamel with occasional dentine involvement. In contrast to linear enamel hypoplasia (LEH), LHPC are non-linear, form on the facial aspect of the deciduous canines almost exclusively, and typically show no statistically significant differences between males and females within populations (Guatelli-Steinberg and Lukacs, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of living children have shown that differential treatment of males and females in childhood can predict differences in levels of LEH in adulthood (May et al, 1993). Moreover, from the investigation of enamel hypoplasia in deciduous and permanent dentition of human and nonhuman primates, Guatelli-Steinberg and Lukacs (1999) insisted that though females are better buffered against environmental stress, a weak influence of male vulnerability on the expression of enamel hypoplasia is most likely to be detected in samples of very large size (>1000 individuals), and that evidence of higher enamel hypoplasia prevalence in girls might therefore be used as a biological marker of preferential investment in sons.…”
Section: Sex Differencesmentioning
confidence: 99%
“…It is argued that deciduous dental enamel defects are good indicators of permutations in amelogenesis from the second trimester to the end of the first year of life (Goodman and Rose, 1990a). The importance of looking at deciduous teeth and the defects specific to these teeth is becoming recognised both in archaeological and modern human and non-human primate studies (e.g., Guatelli-Steinberg and Lukacs, 1999;Lukacs, 1999;Skinner and Newell, 2003), but still few bioarchaeological studies collect these data or report on these defects, compared with the vast number that investigate LEH in permanent teeth.…”
Section: Deciduous Dental Enamel Defectsmentioning
confidence: 99%